RISK FACTORS FOR SEXUAL DYSFUNCTION IN JAPANESE TESTICULAR CANCER SURVIVORS AS EVALUATED BY PATIENT-REPORTED QUESTIONNAIRE - Soichiro Ogawa; Ruriko Honda-Takinami; Kanako Matsuoka; Seiji Hoshi; Tomoyuki Koguchi; Junya Hata; Yuichi Sato; Hidenori Akaihata; Masao Kataoka; Nobuhiro Haga; Yoshiyuki Kojima (Journal of Cancer Rehabilitation, 2022)
Background Since survival rates for testicular malignant germ cell cancer (TC) are favorable, quality of life is of major interest for survivors in subsequent life. TC survivors reportedly have sexual concerns and anxieties after rehabilitation. Understanding the effects of TC treatment on sexual function is therefore quite important. On the other hand, data about sexual function in healthy men vary considerably among nations. Knowing what factors in uence sexual function in Japanese survivors is thus meaningful. The present study evaluated clinical factors that affect post-treatment sexual function as assessed by patient-reported questionnaire among Japanese TC survivors. Methods A total of 28 patients who were diagnosed with TC between April 2004 and March 2020 were analyzed in this study. Multivariable analyses were conducted to identify factors associated with sexual function after TC treatment. Sexual function was assessed by the International Index of Erectile Function-15, a patient-reported questionnaire. Results On multivariable analyses, increases in numbers of cisplatin-based chemotherapy cycles were associated with decreased erectile function (odds ratio: 0.47, p = 0.048), orgasmic function (odds ratio: 0.297, p = 0.04) and intercourse satisfaction (odds ratio: 0.483, p = 0.043). Conclusions Increased cycles of cisplatin-based chemotherapy was the factor associated with decreases in erectile function, orgasmic function and intercourse satisfaction among Japanese TC survivors. Based on these data, we propose that patients diagnosed with TC should be informed before treatment about the risks to sexual dysfunction of increased cycles of cisplatin-based chemotherapy.